1996
DOI: 10.1177/106002809603000614
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Dornase Alfa in the Treatment of Cystic Fibrosis

Abstract: Dornase alfa appears to produce small but sustained improvements in lung function in patients with cystic fibrosis. It may also slow the progression of pulmonary disease. Infection rates appear to be reduced, which may well have important long-term consequences. However, evidence to date has not clarified the most appropriate use of dornase alfa in the treatment of cystic fibrosis. Whether quality of life is affected in a meaningful and measurable way is yet to be clarified. A trial of the drug in patients wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

1998
1998
2018
2018

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 13 publications
0
7
0
Order By: Relevance
“…As reports of the G‐CSF priming of neutrophils to form NETs are numerous, anti‐G‐CSF may be useful to prevent NETs in patients. This is likely to be more successful than the administration of an agent such as DNase to disrupt other NET components, which is currently in use for cystic fibrosis . Thus, strategies disrupting G‐CSF signalling require further investigation in vivo , especially with regard to effects on non‐tumour‐induced granulopoiesis that is required to fight infection.…”
Section: Neutrophils and G‐csf As Therapeutic Targetsmentioning
confidence: 99%
“…As reports of the G‐CSF priming of neutrophils to form NETs are numerous, anti‐G‐CSF may be useful to prevent NETs in patients. This is likely to be more successful than the administration of an agent such as DNase to disrupt other NET components, which is currently in use for cystic fibrosis . Thus, strategies disrupting G‐CSF signalling require further investigation in vivo , especially with regard to effects on non‐tumour‐induced granulopoiesis that is required to fight infection.…”
Section: Neutrophils and G‐csf As Therapeutic Targetsmentioning
confidence: 99%
“…19 Its safety was well established and its short term efficacy seemed reasonable, but its long term efficacy and specific indications for its use in patients with cystic fibrosis were not apparent 2021…”
Section: Discussionmentioning
confidence: 99%
“…When dornase-alfa was compared to hypertonic saline, it was found to result in a mean improvement in FEV1 of 8% at a mean additional cost of £1 409 over a 12-week period. In addition, using alternate-day dornase-alfa was not a cost-effective alternative in comparison with daily treatment for the same period 20. In general, clinical trials in CF have shown improvements in lung function 21.…”
Section: Practical Examples Of the Usefulness Of Pharmacoeconomic Anamentioning
confidence: 98%
“…It is considered an effective mucolytic and is indicated in conjunction with standard therapies for cystic fibrosis (CF). Clinical trials have indicated a small improvement in forced expiratory volume in 1 second (FEV1) and forced vital capacity (FVC), but whether quality of life is affected in a meaningful and measurable way is yet to be clarified 1820. When dornase-alfa was compared to hypertonic saline, it was found to result in a mean improvement in FEV1 of 8% at a mean additional cost of £1 409 over a 12-week period.…”
Section: Practical Examples Of the Usefulness Of Pharmacoeconomic Anamentioning
confidence: 99%